Perceptions of the risk of drowning at surf beaches among New Zealand youth. Issue 4 (2nd October 2018) - Willcox-Pidgeon, Stacey; Kool, Bridget; Moran, Kevin
ABSTRACT: In many countries, beaches are a high-risk location for drowning. In New Zealand, youth and young adults are particularly at risk of drowning at beaches, accounting for 17.4% of drowning deaths and 18.4% of rescues at surf beaches between 2008 and 2013, over 90% of fatalities were male. This study explored New Zealand youth risk perceptions of drowning and their coping appraisal processes at a surf beach. A cross-sectional survey of high school students ( n = 599) was conducted between February and April 2014. Females and non-New Zealand European students reported higher levels of perceived vulnerability and severity of drowning risk, and New Zealand European students reported higher levels of self-efficacy of preventive actions. By addressing the underlying causes of underestimation of risk and overestimation of ability, these findings can be utilized to increase awareness and to enhance water safety risk strategies for youth, especially males, in the surf beach setting.